Hospital Malnutrition in Pediatric Surgery at dr. Cipto Mangunkusumo General Hospital 2015 and Its Associated Factors - Cendrawan, Novi Kurnia; Budianto, Iskandar R. (The New Ropanasuri Journal of Surgery, 2019)
Introduction. Hospital malnutrition is known to increase the length of stays, mortality, and morbidity, however, the factors associated with the development of hospital malnutrition, especially in pediatric surgery patient population, has not been recognized. Method. This study was done to evaluate the occurrence of hospital malnutrition in pediatric surgery population and to identify the factors associated with hospital malnutrition. Primary data was gathered from pediatric surgery patients hospitalized in the pediatric surgery ward of Dr. Cipto Mangunkusumo General Hospital within July–December 2015. Data on age, diagnosis, nutrition status at admission, whether any procedure was done during a hospital stay, fasting duration, duration of surgery, length of stays and classification of surgical procedure done were collected. Univariate and multivariate analysis was done to identify the association between these variables and hospital malnutrition. Results. Out of 198 patients admitted in the pediatric surgery ward, 50 subjects were enrolled. The occurrence of hospital malnutrition among these subjects was 40%. Among the categorical variables (age, diagnosis, nutrition status at admission, whether any procedure was done during a hospital stay, classification of surgical procedure) only the classification of surgical procedure was found to be significantly associated with hospital malnutrition (p = 0.013). Meanwhile, among the numerical variables (fasting duration, duration of surgery, length of stays) only postoperative length of stays was correlated with hospital malnutrition (p = 0.009). Conclusion. It can be inferred that the burden of surgery is associated with hospital malnutrition, and in turn, hospital–malnutrition is associated with increased postoperative length of stays.